SOSIALISASI PEMBUATAN PUPUK BOKASHI DARI SEKAM PADI DAN POC (PUPUK ORGANIK CAIR) DARI AKAR BAMBU DI DESA SIKUR SELATAN, LOMBOK TIMUR - fadilah, Nurulfadilah; Fitrianti, Linda; Handayani, Dei; Intan; Putri Meylita, Anggi; Dhaifullah, M. Naufal; Syanhabi, Aan; Dharmawan, Wawan; Alisukma, M. Taufan; Suryaningsih, Liana; Munir, Muhammad; fadilah, Nurul (Jurnal Wicara, 2025)
South Sikur Village is one of the villages in Sikur sub-district, East Lombok Regency, West Nusa Tenggara. One of the potentials owned by Sikur Selatan Village is in the field of agriculture which is estimated to be more than 60% of the total village land area. The use of chemical fertilisers is the main method used by the village community. The application of organic farming such as using bokashi and POC fertilisers is a simple step and the materials needed are abundant in nature. In addition, the use of organic fertilisers can improve the physical, chemical, and biological properties of the soil so that it supports plant growth. The purpose of this service is to provide understanding and training for the Sikur Selatan Village community, the majority of whom are farmers, to utilise the village potential in the form of rice husks and bamboo roots into bokashi fertiliser and POC for sustainable agriculture. The method used is the socialisation of making bokashi fertiliser and POC. Farmers' understanding of the material provided can be seen from the enthusiasm of the community during the activity so that farmers gain new knowledge to be more skilled in utilising village potential.